Evidence-based public health: concepts, principles and applications to promote physical activity in the Brazilian context - Leonardo Augusto Becker; Cassiano Ricardo Rech; Rodrigo Siqueira Reis (Universidade Federal de Santa Catarina, 2019)
The aim of this study was to present the Evidence-Based Public Health (EBPH), describing its concept, principles, application, and relate these theoretical elements for the promotion of Physical Activity (PA) in Brazil. A narrative research on EBPH was conducted in books and in the PUBMED database in 2017. EBPH stages comprise aspects widely disseminated in the public health area, which are beginning to be used for the promotion of PA in Brazil. The use of these concepts can improve Evidence-Based Decision Making (EBDM) through various aspects, including greater access to key scientific evidence, communication between those responsible for EBDM and researchers, in addition to investments in qualification of health professionals.